Intramolecular Diels–Alder Reactions of Cyclopropenone Ketals - Patel, Paresma R. (2010)
[Image: see text] The first intramolecular cycloaddition reactions of cyclopropenone ketals with tethered electron-deficient, electron-rich, and neutral 1-substituted dienes are reported, constituting inverse electron demand, normal, and neutral Diels-Alder reactions, that provide exclusively the exo [4 + 2] cycloaddition products without the intervention of [1 + 2], [3 + 2], or [3 + 4] cycloadducts in reactions whose course do not depend on the reaction conditions, the diene activating substituent, or the nature of the tethering.